Total laparoscopic hysterectomy using a percutaneous surgical system: a pilot study towards scarless surgery. (August 2016) - Rossitto, Cristiano; Gueli Alletti, Salvatore; Rotolo, Stefano; Cianci, Stefano; Panico, Giovanni; Scambia, Giovanni
Abstract: Objective: The evolution of minimally invasive surgery has moved beyond reduction of surgical trauma while maintaining adequate efficacy and safety standards. Percuvance™ Percutaneous Surgical System (PSS) instruments represents the last novelty in this panorama. Consisting of less than 3 mm laparoscopic shaft introduced percutaneously with an interchangeable 5 mm tool installed in place of the needle tip, they combine micro-invasiveness and operative performance. Study design: We prospectively collected and retrospectively analyzed data of 10 cases of laparoscopic total hysterectomy with Percuvance™ PSS for benign or early malignant gynecological diseases in order to assess the capability and safety of this new device. Data were recorded in a prospectively designed clinical database including patient demographics characteristics, operative data, intra- and postoperative complications, conversion rate, length of hospital stay and cosmetic outcome. Results: The reported series consisted of 10 patients undergoing total laparoscopic hysterectomy with a median age of 51.5 years (range 44–72 years) and a median BMI (body mass index) of 25.3 (range 19.7–30.4). All patients had bilateral salpingo-oophorectomy or bilateral salpingectomy and two of them underwent pelvic lymphadenectomy. A median operative time of 67 min (range 45–180 min) and a median estimated blood loss (EBL) of 50 ml (range 10–100 ml) were registered. Median PSS introduction time was 5 min (range 3–10 min). No conversions to standard laparoscopy or laparotomy were required and no intraoperative complications occurred. Discharge was on day 1 in 4 cases, on day 2 in the other 6 cases. All patients conveyed complete satisfaction with the cosmetic result and postoperative pain control. No complications were registered within 30 days after surgery. Conclusions: PSS total laparoscopic hysterectomy is safe and feasible with good results in terms of operative time, cosmesis, postoperative pain, recovery and short hospitalization. Further studies are needed to compare PSS total hysterectomy to conventional multi-access laparoscopic and other mini-invasive approaches.